NUDT15 Genetic Variants in Chinese Han, Uighur, Kirghiz, and Dai Nationalities - Zhang, Fang; Amat, Gulbanur; Tang, Yanjing; Chen, Ru; Tian, Xin; Hu, Wenting; Chen, Changcheng; Shen, Shuhong; Xie, Yangyang (Frontiers in Pediatrics, 2022)
Background: Thiopurines are widely used as anti-cancer and immunosuppressant agents, but have a narrow therapeutic index owing to frequent toxicity and life-threatening bone marrow suppression. The nudix hydrolase 15 (NUDT15) genetic polymorphism is strongly associated with the tolerance and myelosuppressive effect of mercaptopurine administration, but the frequency of NUDT15 variants is known to vary among different ethnic groups or nationalities. At present, the NUDT15 gene polymorphism in ethnic minorities such as the Uighur, Kirghiz, and Dai nationalities in China is unclear. Procedure: DNA samples were isolated from 1,071 Chinese children, including 675 Han children with acute lymphoblastic leukemia and 396 healthy minority children, including 118 Uighur, 126 Kirghiz, and 152 Dai participants. The coding regions of NUDT15 exons 1 to 3 were amplified by polymerase chain reaction. NUDT15 genotypes were identified by Sanger sequencing. Results: Five NUDT15 genetic variants of coding regions including rs746071566 (c.55_56insGAGTCG), rs186364861 (c.52G>A), c.137C>G, and c.138T>G in exon 1, and the variant rs116855232 (c.415C>T) in exon 3 were found among the participants. The frequency of NUDT15 rs746071566 variants was lower in the Uighur and Kirghiz populations than in the Han population and in other East Asian nationalities, while the frequency of c.415C>T variants was lower in the Dai population. The c.52G>A variant was relatively uncommon in children of the Han, Uighur, Kirghiz, and Dai ethnic groups. Notably, the rare variants c.137C>G and c.138T>G in a Uighur child were predicted to be disruptive sites. Conclusions: In summary, our results illustrate the NUDT15 polymorphisms in Chinese children of Han, Uighur, Kirghiz, and Dai nationalities, and provide the most effective detection recommendations for different ethnic groups to predict thiopurine-related toxicity, which could be used to guide future clinical thiopurine dose adjustment.